Students’ Visual Reasoning Ability in Solving Quadratic Function in Terms of Learning Style - Masduki, Masduki; Savitri, Dhea; Khotimah, Rita Pramujiyanti (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Visual reasoning plays an important role in problem-solving and the success of the student’s learning mathematics. This study aims to reveal the students’ visual reasoning ability in solving quadratic function problems in terms of activist, reflector, and pragmatic learning styles. This research used a qualitative approach with a case study were 30 9th-Grade students at one of the public junior high schools in Karanganyar District, Central Java, Indonesia. The Learning Style Questionnaire (LSQ) from Honey and Mumford was used to categorize the students’ learning style. In each category, the researcher selected two students purposively to be interviewed. The researchers used two quadratic equation problems to explore the students’ visual reasoning profile. Before being used, the questions were validated by two experts in mathematics education. The result showed that students with activist learning styles unable to demonstrate all indicators of visual reasoning. The students with pragmatics learning style can exhibit only one indicators of reasoning, namely interpretation. Then, students with reflector and theoretical learning style able to perform all indicators of visual reasoning. Thus, it can be concluded that the student’s learning style affect the visual reasoning ability in solving quadratic function.